The Routledge International Handbook of Criminology and Human Rights - Weber, Leanne; Fishwick, Elaine; Marmo, Marinella (Taylor & Francis, 2017)
The Routledge International Handbook of Criminology and Human Rights brings together a diverse body of work from around the globe and across a wide range of criminological topics and perspectives, united by its critical application of human rights law and principles. This collection explores the interdisciplinary reach of criminology and is the first of its kind to link criminology and human rights. This text is divided into six sections, each with an introduction and an overview provided by one of the editors. The opening section makes an assessment of the current standing of human rights within the discipline. Each of the remaining sections corresponds to a substantive area of harm prevention and social control which together make up the main core of contemporary criminology, namely: -criminal law in practice; -transitional justice, peacemaking and community safety; -policing in all its guises; -traditional and emerging approaches to criminal justice; -and penality, both within and beyond the prison. This Handbook forms an authoritative foundation on which future teaching and research about human rights and criminology can be built. This multi-disciplinary text is an essential companion for criminologists, sociologists, legal scholars and political scientists.